High‐Transconductance Organic Electrochemical Transistor Fabricated on Ultrathin Films Using Spray Coating. Issue 3 (21st December 2020) - Nishinaka, Masaya; Jinno, Hiroaki; Jimbo, Yasutoshi; Lee, Sunghoon; Wang, Jiabin; Lee, Wonryung; Yokota, Tomoyuki; Someya, Takao
Abstract : Organic electrochemical transistors (OECTs) are widely used for monitoring electrophysiological activities by exploiting advantages, such as flexibility, biocompatibility, low‐voltage operation, and high transconductance. Transconductance is a major factor that determines the sensitivity of OECT‐based sensors. In comparison with other field‐effect transistors, the transconductance of OECTs having the poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) channel layer is proportional to the channel thickness because the entire film acts as a channel. Therefore, the formation of a thick channel layer is essential for OECTs. However, it is difficult to form a thick film by spin coating. Herein, spray coating is introduced, and a thick and uniform PEDOT:PSS layer (1.05 μm) is successfully formed by controlling the compressed air pressure and number of coating cycles. Moreover, a high‐transconductance (7.5 mS) ultraflexible OECT with a sufficiently rapid response is fabricated (2.3 kHz). Abstract : A simple deposition process of thick and smooth poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) films with high controllability of film thickness using a spray coating technique is developed. Using this technique, high transconductance, and sufficiently rapid time response, organic electrochemical transistors on ultrathin substrate with a thick spray‐coated PEDOT:PSS channel layer are demonstrated.